Expression of phosphatidylcholine biosynthetic enzymes during early embryogenesis in the amphibian Bufo arenarum. Issue 2 (15th November 2013) - Fernández-Bussy, Rodrigo; Mouguelar, Valeria; Banchio, Claudia; Coux, Gabriela
Summary: In the principal route of phosphatidylcholine (PC) synthesis the regulatory steps are catalysed by CTP:phosphocholine cytidylyltransferase (CCT) and choline kinase (CK). Knock-out mice in Pcyt1a (CCT gene) and Chka1 (CK gene) resulted in preimplantation embryonic lethality, demonstrating the essential role of this pathway. However, there is still a lack of detailed CCT and CK expression analysis during development. The aim of the current work was to study the expression during early development of both enzymes in the external-fertilization vertebrate Bufo arenarum . Reverse transcription polymerase chain reaction (RT-PCR) and western blot confirmed their presence in unfertilized eggs. Analysis performed in total extracts from staged embryos showed constant protein levels of both enzymes until the 32-cell stage: then they decreased, reaching a minimum in the gastrula before starting to recover. CTP:phosphocholine cytidylyltransferase is an amphitropic enzyme that inter-converts between cytosolic inactive and membrane-bound active forms. Immunoblot analysis demonstrated that the cytosolic:total CCT protein ratio does not change throughout embryogenesis, suggesting a progressive decline of CCT activity in early development. However, PC (and phosphatidylethanolamine) content per egg/embryo remained constant throughout the stages analysed. In conclusion, the current data for B. arenarum suggest that net synthesis of PC mediated by CCT and CK is not required in early development and that supplies for membrane biosynthesis are fulfilled by lipids already present in the egg/embryo reservoirs.